The prevalence of psychological comorbidity in people with vitiligo: a systematic review and meta‐analysis. (1st April 2018) - Osinubi, O.; Grainge, M.J.; Hong, L.; Ahmed, A.; Batchelor, J.M.; Grindlay, D.; Thompson, A.R.; Ratib, S.
Summary: Background: Vitiligo is a chronic disorder causing skin depigmentation with global prevalence varying from 0·2% to 1·8%. U.K. guidelines recommend assessment of psychological state during clinical evaluation of vitiligo. However, the prevalence of psychological comorbidity in people with vitiligo has not been described. Objectives: To establish the prevalence of psychological symptoms or disorders in people with vitiligo and describe the outcome measures used. Methods: We performed a comprehensive search of MEDLINE, Embase, CINAHL and PsycINFO to identify observational studies assessing the prevalence of psychological symptoms or disorders (December 2016). DerSimonian and Lard random‐effects models were used to estimate the overall pooled prevalence. Results: We identified 29 studies with 2530 people with vitiligo. Most studies included a measure of either depression ( n = 25) or anxiety ( n = 13). The commonest tools were the Hospital Anxiety and Depression Scale and the Centre for Epidemiology Studies Depression Scale. Ten studies provided information on 13 other psychological outcomes. Pooled prevalence using depression‐specific and anxiety‐specific questionnaires was 0·29 [95% confidence interval (CI) 0·21–0·38] and 0·33 (95% CI 0·18–0·49), respectively. Prevalence was lower for clinically diagnosed depression (0·21, 95% CI 0·15–0·28) and anxiety (0·15, 95% CI 0·06–0·24). When nonspecific tools were used the prevalence remained similar for depression (0·27, 95% CI 0·08–0·46) but increased for anxiety (0·46, 95% CI 0·39–0·52). High heterogeneity was observed. Conclusions: A range of psychological outcomes are common in people with vitiligo. The prevalence of anxiety was influenced by type of screening tool, suggesting the need for validation of psychological outcome screening tools in the field of dermatology.